2022
DOI: 10.1177/13591053221081905
|View full text |Cite
|
Sign up to set email alerts
|

Men’s and women’s endorsement of hegemonic masculinity and responses to COVID-19

Abstract: Using a gendered psychology of health approach, we examine the effects of the culturally idealized form of masculinity—hegemonic masculinity—for both men and women’s health attitudes and behaviors. Using data collected across four studies ( N = 805) during the COVID-19 pandemic, we found that stronger endorsement of hegemonic masculinity related to health attitudes antithetical to mitigation strategies (e.g. more engagement in risky behaviors, less support for federal mandates) and evaluations of how political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 83 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…These findings add support to emerging literature that demonstrates the importance of masculinity-related constructs on men's health behavior related to COVID-19. [13][14][15][16][17]38 The findings extend the current literature by being the first to our knowledge to examine gender role discrepancy and discrepancy stress in relations to COVID-19 prevention, and by exploring whether the effect of discrepancy stress varies by race/ethnicity, sexual orientation, and income. The findings broadly suggest that gender role discrepancy was associated with better engagement in vaccination, while discrepancy stress had a negative The interaction between race/ethnicity and gender role discrepancy stress on vaccination status.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings add support to emerging literature that demonstrates the importance of masculinity-related constructs on men's health behavior related to COVID-19. [13][14][15][16][17]38 The findings extend the current literature by being the first to our knowledge to examine gender role discrepancy and discrepancy stress in relations to COVID-19 prevention, and by exploring whether the effect of discrepancy stress varies by race/ethnicity, sexual orientation, and income. The findings broadly suggest that gender role discrepancy was associated with better engagement in vaccination, while discrepancy stress had a negative The interaction between race/ethnicity and gender role discrepancy stress on vaccination status.…”
Section: Discussionsupporting
confidence: 66%
“…8,9 Studies in the U.S. demonstrate adherence to traditional masculine norms is generally associated with less healthcare utilization, such as lower health literacy, less HIV or sexually transmitted infection (STI) testing, and less psychological help seeking behavior. [10][11][12] Several studies report conforming to traditional masculine norms associates with lower adherence to CDC-recommended COVID-19 prevention behaviors, [13][14][15][16][17] but the research in this area is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that examine COVID-19 outcomes through the lens of adherence to traditional masculine/feminine norms similarly report strict adherence to associate with less prevention behavior. [89][90][91] Future research should explore adherence to social structures of gender further, rather than just identification with binary categories of male/female or man/ woman, in relation to vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether it be his unwillingness to self-censor racist or misogynist remarks, his presumed managerial business acumen, or his desire to "fight" anyone who dared challenge him; in each case, Trump was a desirable candidate to his supporters because he was not exuding a hybrid masculinity (Dignam and Rohlinger 2019;Dignam et al 2021). Similarly, Vescio and Schermerhorn (2021) found that Americans who associated masculinity with toughness, status, and a lack of feminine practices were more likely to view Trump favorablyincluding how he responded to the pandemic (Schermerhorn and Vescio 2023).…”
Section: Gender Populism and The Trump Presidencymentioning
confidence: 99%